2010
DOI: 10.1016/j.nlm.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Directional learning, but no spatial mapping by rats performing a navigational task in an inverted orientation

Abstract: Previous studies have identified neurons throughout the rat limbic system that fire as a function of the animal's head direction (HD). This HD signal is particularly robust when rats locomote in the horizontal and vertical planes, but is severely attenuated when locomoting upside-down (Calton & Taube, 2005). Given the hypothesis that the HD signal represents an animal's sense of its directional heading, we evaluated whether rats could accurately navigate in an inverted (upside-down) orientation. The task requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…When the inverted animals were released from a familiar test location they needed to use landmarks within the room to establish a directional bearing to the correct escape hole. They also had to discriminate their visual views between the two start locations in order to head in the correct direction (see [4] for details). During the Center condition trials, the inverted rats were placed in an unfamiliar location (the maze center) and had to use their representation of landmarks in the environment to compute their directional orientation and an accurate route to the escape hole.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the inverted animals were released from a familiar test location they needed to use landmarks within the room to establish a directional bearing to the correct escape hole. They also had to discriminate their visual views between the two start locations in order to head in the correct direction (see [4] for details). During the Center condition trials, the inverted rats were placed in an unfamiliar location (the maze center) and had to use their representation of landmarks in the environment to compute their directional orientation and an accurate route to the escape hole.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that the HD signal is disrupted when the animal is positioned in an inverted plane either under 1-g or 0-g conditions [5, 6]. In addition, a recent study demonstrated that inverted rats were unable to learn to navigate to an escape hole unless they were released from one of two familiar locations [4]. When released from novel locations, they were unable to reach the escape hole, despite the presence of familiar visual landmarks within the environment and the fact that the escape hole was < 1 m from the release point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A navigating animal is thought to have two sources of information with which it can locate itself within an environment: egocentric and allocentric (Pearce et al 1998;Aggleton et al 2000;Begega et al 2001;Valerio et al 2010). In egocentrically based navigation, animals can use view-dependent information, whereby any available external information (e.g., cues or landmarks) is represented in relation to the animal itself (Brown 1992;Maurer and Derivaz 2000).…”
mentioning
confidence: 99%
“…In one study (Valerio et al, 2010), rats performed a spatial task while inverted. In this task, a circular board was hung from the ceiling with four identical escape holes spaced equally apart.…”
Section: Importance Of Vestibular Inputs For Navigationmentioning
confidence: 99%